The mediating role of emotion dysregulation and depression on the relationship between childhood trauma exposure and emotional eating() - Michopoulos, Vasiliki (Appetite, 2015)
Exposure to childhood adversity is implicated in the etiology of adverse health outcomes, including depression, posttraumatic stress disorder (PTSD), and obesity. The relationship between childhood trauma and obesity may be related to the association of childhood trauma and risk for emotional eating. One pathway between trauma exposure, psychopathology, and emotional eating may be through emotion dysregulation and depression. The current study was undertaken to characterize demographic, environmental, and psychological risk factors for emotional eating in a primarily African American, low socioeconomic status (SES), inner-city population (N = 1110). Emotional eating was measured using the Dutch Eating Behavioral Questionnaire and the Emotional Dysregulation Scale was used to assess emotion regulation. The Beck Depression Inventory and the modified PTSD Symptom Scale were used to assess depression and PTSD, respectively. Higher levels of emotional eating were associated with body mass index, income, childhood and adulthood trauma exposure, depressive and PTSD symptoms, negative affect and emotion dysregulation. Childhood emotional abuse was the most associated with emotional eating in adulthood. Hierarchical linear regression and mediation analyses indicated that the association between childhood trauma exposure (and emotional abuse specifically) and emotional eating was fully mediated by depression symptoms and emotion dysregulation, with emotional dysregulation contributing more to the mediation effect. Together these findings support a model in which obesity and related adverse health outcomes in stress- and trauma-exposed populations may be directly related to self-regulatory coping strategies accompanying emotion dysregulation. Our data suggest that emotion dysregulation is a viable therapeutic target for emotional eating in at-risk populations.